TRANSFORMASI PENDIDIKAN MODERN: PERAN ILMU PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA DIGITAL - Ramadhan, Al Hafiz Rasya (Universitas Tanjungpura, 2025)
The transformation of modern education is a global phenomenon characterized by fundamental changes in paradigms, approaches, and education delivery systems at various levels. The development of digital technology, socio-cultural dynamics, and the demands of globalization have encouraged the world of education to continue to adapt and innovate. In this context, education science plays a central role as a theoretical foundation as well as a practical instrument that directs the process of change in a systematic, contextual, and futureoriented manner. This article aimsto examine in depth the contribution of education science in supporting the transformation of modern education through a descriptive qualitative approach based on literature study. Scientific sources used include academic journals, books, policy documents and relevant articles from the last three years. The results of the study show that education science plays a role in various crucial aspects of transformation, including in updating the learning paradigm towards a student-centered approach, developing a competency-based curriculum, and integrating technology pedagogically. In addition, education science also strengthens the role of teachers as facilitators and innovators, encourages digital literacy and character education, and supports the birth of inclusive and equitable education policies. Concepts such as lifelong learning, local value-based education, and the humanization of learning are important dimensions in education science.